Uji Organoleptik dan Fisik Wine Coffee dari Kopi Tepal Sumbawa - Noni Kusriani; Samuyus Nealma; Veni Rori Setiawati (Program Studi Teknologi Hasil Pertanian, 2023)
Wine coffee is a type of coffee that comes from a post-harvest process that is processed through a fermentation process to produce a unique taste resembling the aroma of wine. Therefore, wine coffee is also often referred to as fermented coffee and the aroma in coffee wine is produced by the overhauling of compounds due to the metabolism of microorganisms in the fermentation process. However, the strong aroma and taste of coffee wine does not diminish the original taste of coffee. The purpose of this study was to determine the organoleptic and physical tests of wine coffee from SUMBAWA tepal coffee. This research was conducted for 3 months. The changes observed in this study were organoleptic tests, color physical tests, and pH. From the organoleptic test results, color, taste, and aroma were more dominant on the somewhat liking scale and the strong scale on the level of liking (hedonic) and acceptance (scoring). Whereas on the physical test, the color brightness (L *) shows a bright color indication, because it is above the 50 step. And the pH is on the acid scale.